Profile of the Interpreting Ability of Students on Static Fluid - Nurmisanti Nurmisanti; Yudi Kurniawan; Riski Muliyani (International Journal of Multi Discipline Science, 2020)
The purpose of this study was to get a description of the students' ability to interpret the static fluid material. This research was a quantitative descriptive study and the sample was taken by purposive sampling technique with a total sample of 26 students at one of the Madrasah Aliyah in the city of Singkawang. To achieve this goal, students had filled in questions about static fluids in a multiple-choice test. The results of this study were a quantitative description of the student's ability to interpret the static fluid material. The interpretive ability category was adapted from the n-gain category. The results showed that the category of students' ability to interpret the concept of hydrostatic pressure and Archimedes principle was in the high category with a percentage of 88% and on the Pascal principle it was categorized as low with a percentage of 19%. The results of this study can be a reference for future researchers to improve aspects of understanding interpreting categories in students.